The effects of listener training on the development of analogical reasoning. Issue 2 (12th September 2019) - Meyer, Careen S.; Cordeiro, Maria Clara; Miguel, Caio F.
Abstract : We evaluated the effects of listener training on the emergence of analogical reasoning, as measured via equivalence‐equivalence and explored the role of verbal behavior when solving analogy‐type tasks. We taught 18 college students to select component stimuli from 2 classes, labeled "vek" and "zog, " and evaluated tacts and relational responding in the presence of baseline (AB and BC), symmetry (BA and CB), and transitivity (AC and CA) compounds. In Experiment 1, 5 out of 6 participants passed analogy tests, but none of them engaged in the relational tacts "same" and "different" during tact tests, possibly due to lack of instructional control. A change in instructions during Experiment 2 produced relational tacts in 4 of 6 participants, and 5 participants passed analogy tests. In Experiment 3, we implemented a talk‐aloud procedure to determine if the participants were emitting relational tacts during analogy tests. All 6 participants tacted stimuli relationally and engaged in problem‐solving statements to solve analogy tests. Results from these studies suggest that listener and speaker behavior in the form of relational tacts and other problem‐solving statements influenced the participants' equivalence–equivalence performance.